A facile route to grain morphology controllable perovskite thin films towards highly efficient perovskite solar cells. (November 2018) - Zhang, Fuguo; Cong, Jiayan; Li, Yuanyuan; Bergstrand, Jan; Liu, Haichun; Cai, Bin; Hajian, Alireza; Yao, Zhaoyang; Wang, Linqin; Hao, Yan; Yang, Xichuan; Gardner, James M.; et al.
Abstract: Perovskite photovoltaics have recently attracted extensive attention due to their unprecedented high power conversion efficiencies (PCEs) in combination with primitive manufacturing conditions. However, the inherent polycrystalline nature of perovskite films renders an exceptional density of structural defects, especially at the grain boundaries (GBs) and film surfaces, representing a key challenge that impedes the further performance improvement of perovskite solar cells (PSCs) and large solar module ambitions towards commercialization. Here, a novel strategy is presented utilizing a simple ethylammonium chloride (EACl) additive in combination with a facile solvent bathing approach to achieve high quality methyammonium lead iodide (MAPbI3 ) films. Well-oriented, micron-sized grains were observed, which contribute to an extended carrier lifetime and reduced trap density. Further investigations unraveled the distinctively prominent effects of EACl in modulating the perovskite film quality. The EACl was found to promote the perovskite grain growing without undergoing the formation of intermediate phases. Moreover, the EACl was also revealed to deplete at relative low temperature to enhance the film quality without compromising the beneficial bandgap for solar cell applications. This new strategy boosts the power conversion efficiency (PCE) to 20.9% and 19.0% for devices with effective areas of 0.126 cm 2 and 1.020 cm 2, respectively, with negligible current hysteresis and enhanced stability. Besides, perovskite films with a size of 10 × 10 cm 2, and an assembled 16 cm 2 (5 × 5 cm 2 module) perovskite solar module with a PCE of over 11% were constructed. Graphical abstract: fx1 Highlights: A facile strategy to attain large-area and uniform perovskite films for highly efficient perovskite solar cells is invented. Grain engineering with EACl leads to high quality perovskite film without compromising the perovskite bandgap. Distinctive working mechanism of EACl in this novel strategy was unraveled. Stabilized efficiency of 20.9% with enhanced stability was achieved. The perovskite films with size 10×10 cm2 and the solar cell sub-modules with size 5×5 cm2 were successfully assembled.